Screening for dementia using picture memory impairment screen among older adults in an urban underprivileged area of Bangalore city, India - Mathew, Geethu; Thomas, Seena; R. K., Pretesh; K., Arvind (International Journal Of Community Medicine And Public Health, 2018)
Background: Under detection of dementia is a major challenge in low and middle income countries with 90% of dementia cases remaining unidentified in India. The objective of the study was to assess the prevalence and risk factors of dementia among older adults living in an urban underprivileged area of Bangalore city, India using the picture memory impairment screen (PMIS). Methods: This community based cross sectional study was conducted between September and November 2013 among 202 elderly people in an underprivileged area of Bangalore city. Dementia was defined using a validated cut-off score on the PMIS. Results: The mean age of the participants was 68 years and 65% were illiterate. The overall prevalence of dementia using the screen among elderly people was 15.3%. Age specific prevalence rates were 7.8% (60 to 70), 30.6% (71 to 80) and 61.5% (>80 years) respectively. Increasing age, family history, lower educational and functional status were significantly associated (p<0.05) with dementia. Conclusions: High prevalence of dementia was identified among an urban underprivileged elderly population. The PMIS can be used to triage older adults for further evaluation and management.